(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The contribution aims to identify some emblematic tools in the fight against environmental crime. Starting from the analysis of the environmental asset as a constitutional value, it analyzes, first, the regulatory framework of reference in the light, in particular, of the recent constitutional reform and, subsequently, the critical issues that, on a daily basis, environmental protection must face. It also dwells on the peculiarities of environmental crime and eco-mafias, so as to be able to understand what the main limits are to prevention and contrast actions and, consequently, what are the possible and fundamental solution tools.